Using a chewing simulator for fatigue testing of metal ceramic crowns. (January 2017) - Heintze, S.D.; Eser, A.; Monreal, D.; Rousson, V.
Abstract: Objective: Dynamic loading is a more important predictor for the clinical longevity of ceramic crowns than static loading. However, dynamic loading machines are costly and mostly have only one test station. The SD Mechatronik Chewing Simulator (formerly Willytec) may be a cost-effective alternative to evaluate the fatigue resistance of metal ceramic crowns. Method: Four metal ceramic materials were tested on lower first molar crowns: GC InitiaI, Creation (Willy Geller), IPS InLine (Ivoclar Vivadent) and the new low-fusion IPS Style Ceram (Ivoclar Vivadent). The ceramic material was manually layered on frames made of the nickel-chromium alloy 4all (Ivoclar Vivadent) by using a silicone mould. The crowns were adhesively luted to PMMA dies. Dynamic loading was carried out with a SD Mechatronik Chewing Simulator using additional bars with weights. A steel antagonist (Ø 4 mm) with 40 mm/s downward speed hit the disto-buccal cusp of the crown with minimal impulse while sliding for a distance of 0.7 mm. The starting load was 250 N. The forces at each load level had been verified with a 3D force sensor (Kistler). Four crowns per group and load were submitted to four decreasing load levels for 200, 000 cycles with a resulting simulation frequency of 0.9 Hz and simultaneous thermocycling (5 °C/55 °C) until all four crowns no longer showed chippings. Statistical analyses had been carried out using an exponential, a Weibull and a lognormal model. The fatigue resistance was defined as the maximal load for which one would observe less than 1% failure after 200, 000 cycles. In addition to the fatigue testing of the molar crowns, simulations of finite element method (FEM) were conducted in order to investigate the influence of the mismatch of the thermal expansion coefficient (CTE) between the PMMA die and the molar crown on the fatigue resistance. Results: The 3D-force measurements revealed that the summarised forces were very similar to the force of the dead weights that were put on the bars. The failure modes consisted of cracks and small and big chippings. Chi-square test and Gamma revealed no statistically significant differences between the four test materials in relation to the failure mode. At 250 N all materials showed chippings within the ceramic or down to the metal frame, while at lower loads there were differences. The estimated fatigue resistance was 68 N for GC Initial, 88 N for Creation, 96N for IPS Style Ceram, and 105 N for IPS InLine, when using a Weibull model and considering all possible events. Furthermore, FEM simulations revealed that the maximum values of the maximum principal stress were 90 MPa for the thermocycling and 225 MPa for the external load. Conclusion: The SD Mechatronik Chewing Simulator is an adequate and cost-effective tool to test layered PFM crowns for fatigue resistance. The test method and the chewing simulator can be used for ceramic on metal, ceramic on zirconia and monolithic ceramic materials.